Pengaruh Rasio Aktivitas, Profitabilitas, Struktur Modal, Komite Audit, Dan Ukuran Perusahan Terhadap Pengungkapan Sustainability Report - Nurlaili Ismi; Ai Hendrani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Finding out how factors like activity ratio, profitability, capital structure, audit committee, and business size affect disclosure in sustainability reports is the main goal of this research. The research relied on quantitative data, namely those extracted from the annual report and sustainability report for disclosure purposes. The secondary data included in this study originated from the official corporate website, which can be found at www.idx.co.id. The sample for the research consisted of 128 manufacturing businesses that were listed on the IDX in the basic and chemical industries between 2020 and 2022. The sampling approach yielded a sample of fourteen companies by means of purposive sampling. The study's methodology makes use of causality design, multiple linear regression analysis, and the application capabilities of SPSS 29. The findings demonstrated that the basic and chemical industrial sectors' sustainability reports were simultaneously impacted by the activity ratio, profitability, capital structure, audit committee, and business size. The sustainability report is not significantly impacted by the activity ratio, profitability, or capital structure. The sustainability report is impacted by the audit committee. Sustainability reports are not impacted by a company's size.